Rules for ruin - Matthews, Mimi (Matthews, Mimi. Crinoline academy, 2025)
"No one betrays the Academy. But now Euphemia must decide: break the rules for her enemy, or let the rules break her heart. On the outskirts of London sits a seemingly innocuous institution with a secretive aim - train young women to distract, disrupt, and discredit the patriarchy. Outraged by a powerful politician's systematic attack on women's rights, the Academy summons its brightest - and most bitter - pupil to infiltrate the odious man's inner circle. A deal is struck: bring down the viscount and Miss Euphemia Flite will finally earn her freedom. But betting shop owner Gabriel Royce has other plans. The viscount is the perfect pawn to insulate Gabriel's underworld empire from government interference. He's not about to let some crinoline-clad miss destroy his carefully constructed enterprise - no matter how captivating he finds her threats. From the rookeries of St. Giles to the corridors of Westminster, Euphemia and Gabriel engage in a battle of wits and wills, complicated by a blossoming desire. Soon Euphemia realizes it's not the broken promises to her Academy sisters she should fear, it's the danger to her heart"--